1998
DOI: 10.1139/y98-006
|View full text |Cite
|
Sign up to set email alerts
|

Serum leptin levels and energy expenditure in normal weight women

Abstract: To investigate whether circulating leptin levels are associated with energy expenditure in healthy humans, doubly labeled water energy measurements and food intake assessment were carried out in 27 women (mean age, 48.6 years; weight, 61.9 kg; body mass index, 23.2). Energy expenditure was determined over 13 days. Food intake was measured by 7-day food records. Leptin was measured by radioimmunoassay. Leptin level was strongly associated with percentage body fat (r = 0.59; p < 0.001), fat mass (r = 0.60; p < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 9 publications
3
12
0
Order By: Relevance
“…In humans, a relationship between plasma leptin concentrations and energy expenditure has been observed. 30 Our present observation indicates that carbohydrate overfeeding increases fasting leptin concentrations, but not basal energy expenditure. There was also no correlation between changes in fasting leptin concentration and in 24 h EE.…”
Section: Discussionsupporting
confidence: 41%
“…In humans, a relationship between plasma leptin concentrations and energy expenditure has been observed. 30 Our present observation indicates that carbohydrate overfeeding increases fasting leptin concentrations, but not basal energy expenditure. There was also no correlation between changes in fasting leptin concentration and in 24 h EE.…”
Section: Discussionsupporting
confidence: 41%
“…However, these correlations were found to be independent of changes in body composition only in the study of Doucet et al (45). A positive association between leptin and EE has been described previously in cross-sectional studies pertaining to humans (17)(18)(19)(20)(21). In one study, however, leptin was not controlled for differences in FM (18).…”
Section: Discussionmentioning
confidence: 65%
“…However, in a group of lean and obese 5-year-old Pima Indian children, Salbe et al (17) found that fasting leptin concentration was correlated positively and independently with both total EE assessed by doubly labeled water and with physical activity level. In another study, a nearly significant positive relationship was seen between leptin and EE under free-living conditions in women, after adjusting for differences in body fat percentage (19). Recently Jørgensen and colleagues (21) showed that, in men, leptin is a stronger positive determinant of resting metabolic rate than is FM, whereas the opposite is seen in women.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…leptin (10 mgakgaday for 3 weeks) increased physical activity levels in leptinde®cient obese obaob mice. 21 However, most studies in human subjects have found no relationship between leptin and physical activity levels, 22,23 with only one study in children showing a positive relationship. 24 The apparent inability of leptin to in¯uence physical activity in adult human subjects is also illustrated in a recent study that has shown that the activation of spontaneous physical activity in subjects who are resistant to weight gain after overfeeding is not mediated by leptin.…”
Section: Discussionmentioning
confidence: 99%